Las técnicas de trabajo intelectual en el aprendizaje de los estudiantes del bachillerato en ciencias, especialidad sociales, extensión Hermano Ángel Pastrana Corral, de la Unidad Educativa Fiscomisional a distancia de Loja. Año lectivo 2011 – 2012. Lineamientos alternativos - Briceño Castillo, José Manuel (2013)
This research aims to analyze the characteristics and application of intellectual processes (TTI) in learning by students Baccalaureate Social Extension Angel Pastrana Brother Corral. Investigated for which both teachers and students on the application of the different techniques that are applied study, this information was collected through surveys, and found the following: most students know and apply the TTI in their learning, but no resources which enables them to complete their training, that principals, teachers and students know and use graphic organizers in the teaching-learning process. In addition, I note that the most used by both teachers and the students for teaching and learning, are the guides of work and the lack of a computer center, causes the technique to be used to collect information document review. Moreover the technique to analyze and understand texts used by students is emphasized, while teachers prefer concept maps. Therefore, we consider as positive, in the center of study, teachers and students are aware of the advantages of these techniques and are applying them. But despite the high rates of application of the techniques of intellectual work, their impact on student learning has not been significant. Therefore we concluded that the correlation analysis after it is determined that there is no relationship between intellectual processes and learning. Given this reality Alternative suggested some guidelines in order to further enhance the use of TTI in distance education and converting them into a tool to improve the role of the teacher and student as entities in building their knowledge and interaction within the educational process.